2008
DOI: 10.1016/s0377-1237(08)80145-1
|View full text |Cite
|
Sign up to set email alerts
|

Admission Cardiotocography Screening of High Risk Obstetric Patients

Abstract: The result of admission cardiotocography testing could be used to identify patients likely to develop adverse foetal outcomes and help in optimal utilization of labour room resources.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
31
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(36 citation statements)
references
References 4 publications
5
31
0
Order By: Relevance
“…9 Sandhu et al, have done admission CTG in high risk patients where they found that foetal distress occurred in 15% of reactive group and 73% in non-reactive group. 10 High incidence of foetal distress in our study may be due to inclusion of only high risk cases which correspond with the study by Sandhu et al In present study positive predictive value is 63% for foetal distress with low sensitivity and high specificity as compared to study of Sandhu et al whose PPV is 73%. The sensitivity, specificity, positive predictive value for 5 min APGAR score <7 in our study was 44.4%, 95%, 50% respectively (Table 8) which are corresponding with the study of Sandhu et al study (APGAR score <5).…”
Section: Discussionsupporting
confidence: 88%
“…9 Sandhu et al, have done admission CTG in high risk patients where they found that foetal distress occurred in 15% of reactive group and 73% in non-reactive group. 10 High incidence of foetal distress in our study may be due to inclusion of only high risk cases which correspond with the study by Sandhu et al In present study positive predictive value is 63% for foetal distress with low sensitivity and high specificity as compared to study of Sandhu et al whose PPV is 73%. The sensitivity, specificity, positive predictive value for 5 min APGAR score <7 in our study was 44.4%, 95%, 50% respectively (Table 8) which are corresponding with the study of Sandhu et al study (APGAR score <5).…”
Section: Discussionsupporting
confidence: 88%
“…The findings were similar with the study done by Rahman et al 16 where incidences of NICU admission was significantly high in babies delivered from mother with ominous test group (62%) compared to those with equivocal test group (28%) and reactive test group (3.45%). In study by Sandhu et al 22 neonatal admission to NICU was required in 1% of cases with a reactive AT, 12% of cases with an equivocal AT and 33% of cases with an ominous AT (p<0.01). In a study in Lahore, Noreen et al 23 also found that majority of women with decelerations had most of the abnormal outcomes where 10% of babies were admitted to NICU.…”
Section: Figure 1: Admission Test Resultsmentioning
confidence: 93%
“…In 8.7% of women with ominous AT group, 71.4% had moderate to thick MSL where 64.3% had babies born with Apgar score <7.In this study the evidence of fetal distress was further strengthened by cord blood PH but still the results are very much comparable to the present study. In a study done by Sandhu et al 22 in reactive AT group of 101(67.3%) cases, 4% of babies had Apgar score <7 at five minutes after birth. In equivocal AT group of 34 (22.7%) cases, 26.5% had Apgar score <7 and in ominous AT group of 15(10%) cases, 53.3% had Apgar score <7.…”
Section: Figure 1: Admission Test Resultsmentioning
confidence: 95%
“…Sandhu et al [13] performed admission cardiotocography (CTG) testing in 150 high-risk obstetric cases to predict neonatal outcome and reported that fetal distress during labor developed in 15 % of patients with a normal test and in 73 % of patients with an abnormal test. The admission test had a sensitivity of 66.7 %, specificity of 93.3 % and a positive predictive value of 53.3 % for predicting an Apgar score \5 at birth.…”
Section: Discussionmentioning
confidence: 99%